Pengaruh Bahasa Pertama Terhadap Tindak Tutur Berbahasa Indonesia Siswa SMA Negeri 4 Denpasar - Indriani, Sri; Suparwa, I Nyoman; Putra, Anak Agung Putu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2020)
This research was conducted with the aim of knowing the first language used by students of SMA Negeri 4 Denpasar, knowing and describing Indonesian-speaking speech acts that were taught by SMA Negeri 4 Denpasar students, and knowing the effect of the first language on Indonesian-language acts of students of SMA Negeri 4 Denpasar. This research is a qualitative research using observation and interview methods in data collection. Research findings and analysis results show that the first languages used by SMA Negeri 4 Denpasar students are Balinese, Indonesian and Javanese. In addition, this study also found the influence of the first language in Indonesian language speech acts of SMA Negeri 4 Denpasar students both within the school environment and outside the school environment.